2001
DOI: 10.1006/jmsc.2001.1078
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Themisto (Amphipoda) spp. in the Barents Sea and predator-prey interactions

Abstract: Themisto abyssorum and Themisto libellula were the dominant amphipod species observed in the central and the northern Barents Sea during [1984][1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995][1996]. T. abyssorum was predominant in the subarctic waters, T. libellula in the Arctic waters. A third species, Themisto compressa, was rare and was restricted to the Atlantic waters. Our study showed peak abundances of T. abyssorum and T. libellula in summer and in early autumn. High abundances were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 22 publications
3
76
0
Order By: Relevance
“…Previous investigations in the Greenland Sea during summer revealed that this amphipod species completely dominated the plankton communities in the upper Arctic water layers (Dalpadado et al 1998). Similar observations have been made both in the north-west Atlantic (Percy 1993) and in the Barents Sea, where abundance may reach a peak in early autumn (Dalpadado et al 2001;Dalpadado 2002). P. libellula is assumed to be an important link in the Arctic marine food chain between herbivorous zooplankton and fi sh, birds and mammals (Dunbar 1957;Bradstreet & Cross 1982;Mehlum & Gabrielsen 1993;Dalpadado et al 2001).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Previous investigations in the Greenland Sea during summer revealed that this amphipod species completely dominated the plankton communities in the upper Arctic water layers (Dalpadado et al 1998). Similar observations have been made both in the north-west Atlantic (Percy 1993) and in the Barents Sea, where abundance may reach a peak in early autumn (Dalpadado et al 2001;Dalpadado 2002). P. libellula is assumed to be an important link in the Arctic marine food chain between herbivorous zooplankton and fi sh, birds and mammals (Dunbar 1957;Bradstreet & Cross 1982;Mehlum & Gabrielsen 1993;Dalpadado et al 2001).…”
Section: Discussionsupporting
confidence: 76%
“…Except for the youngest stages, which may occur in the upper water layers during summer, the major hooded seal prey G. fabricii has a typical mesopelagic distribution with occurrence mainly at depths greater than 400 m (Bjørke 2001). This is in contrast to the distribution of the major food of harp seals: the observed krill and amphipod species are usually confi ned to the more upper water layers (< 200 m depth; Dalpadado et al 1998;Dalpadado et al 2001).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…At the same time, in the NW GSL, the arctic (Thysanoessa raschii, Themisto libellula, and Aglantha digitalis) and boreo-arctic (Sagitta elegans and T. abyssorum) (Richard & Haedrich 1991, Percy 1993, Dalpadado et al 1998, 2001) macrozooplankton species were 5 times more abundant in 1998 than in 2000 and 2001. In contrast, the abundance of the more temperate species Meganyctiphanes norvegica (Dalpadado et al 1998(Dalpadado et al ), did not vary significantly between 1998(Dalpadado et al , 2000(Dalpadado et al , and 2001.…”
Section: Interannual Variationsmentioning
confidence: 96%